Pengaruh Jarak Tanam dan Pemberian Pupuk Organik Cair terhadap Pertumbuhan dan Produksi Kedelai Hitam (Glycine max (L) Merril) - Yenti, Elva Wirma; Syafrinal, Syafrinal; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Black soybean production in Indonesia has not been able to meet national consumption. This problem can be overcome by applying liquid organic fertilizer and adjusting the spacing. This study aims to determine the effect of various spacings and concentrations of liquid organic fertilizer on the growth and production of black soybeans. This research was conducted from June to September 2019 using a completely randomized design with three replications. The first factor is the spacing between two levels, namely J1 = Planting distance (40 x 15)cm, J2 = (40 x 20)cm. The second factor is the concentration of liquid organic fertilizer (POC) consisting of 4 levels, namely: K0 = no liquid organic fertilizer + 50 kg.ha-1 Urea, 70 kg.ha-1 TSP, 100 kg.ha-1 KCl, K1= concentration 0.4% + 25 kg.ha-1 Urea, 35 kg.ha-1TSP, 50 kg.ha-1 KCl, K2 = 0.6% concentration + 25 kg.ha-1 Urea, 35 kg.ha-1TSP, 50 kg.ha-1 KCl, K3 = 0.8% concentration + 25 kg.ha-1 Urea, 35 kg.ha-1TSP, 50 kg.ha-1 KCl. Parameters observed consisted of chlorophyll content, flowering plant age, plant height, number of primary branches, harvest age, total number of pods per plant, number of pithy pods, percentage of pithy pods, number of seeds per plant, dry seed weight per plot, dry seed weight. per plant, weight of 100 seeds and harvest index. The results showed that plant spacing had a significant effect on the number of primary branches, the total number of pods per plant, the number of pithy pods, and the number of seeds per plant. The concentration of liquid organic fertilizer has a significant effect on the chlorophyll content. Interaction of plant spacing concentration of liquid organic fertilizer had a significantly affected chlorophyll content and harvest index.Â Keywords: Plant spacing, black soybean, liquid organic fertilize